2006
DOI: 10.1111/j.1540-8159.2006.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Response to Cardiac Resynchronization Therapy: The Selection of Candidates for CRT (SCART) Study

Abstract: Our results confirm the limited value of QRS duration in the selection of patients for CRT. A less-advanced stage of disease and echocardiographic evidence of interventricular dyssynchrony demonstrated to predict response to CRT, while intraventricular dyssynchrony did not predict response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(66 citation statements)
references
References 39 publications
4
58
1
3
Order By: Relevance
“…Although 2 multicenter trials showed that the values >44ms (by SCART group) and 49.2ms (by CARE-HF group) are predictor of echocardiographic response and event free curves after CRT (19,20), in large prospective studies using pulsed wave Doppler, IVDys was not predictive for the effect of CRT (10,12).…”
Section: Interventricular Dysynchronymentioning
confidence: 99%
“…Although 2 multicenter trials showed that the values >44ms (by SCART group) and 49.2ms (by CARE-HF group) are predictor of echocardiographic response and event free curves after CRT (19,20), in large prospective studies using pulsed wave Doppler, IVDys was not predictive for the effect of CRT (10,12).…”
Section: Interventricular Dysynchronymentioning
confidence: 99%
“…M-mode-based variables such as septal-to-posterior wall motion delay have been shown to not be significantly different between responders and nonresponders (23,24). Several other studies have reported the poor predictive value of other variables derived from 2DE platforms (21,25,26). In particular, the recently published PROSPECT trial results highlighted the poor predictive value and significant variability in measuring mechanical dyssynchrony using 12 two-dimensional tissue Doppler-derived parameters (21).…”
Section: Discussionmentioning
confidence: 99%
“…Since only 70-80% of chronic heart failure patients receiving CRT respond to this therapy [1][2][3][4][5], better methods for prediction of response are mandatory. Mechanical dyssynchrony in LV contraction is thought to predict the response to CRT better than electrical dyssynchrony [6][7][8].…”
Section: Introductionmentioning
confidence: 99%